Perspektif Penggunaan Raman Spectroscopy dalam Praktik Klinis dan Bioetika Modern - Nurul Fuji Amandari; Rafika Nur Fadillah; Syahira Fahreza Risdiana; Tri Cahyanto (Pusat Riset dan Inovasi Nasional, 2025)
Raman Spectroscopy is a spectroscopic analysis technique to detect the molecular composition of a sample without damaging it and supports early diagnosis of various diseases and in mapping body tissues with high accuracy. Raman Spectroscopy has various problems that can be associated with bioethical studies such as the problem of biocompatibility of the materials used, challenges in producing consistent results, and the safety of laser use in patients. The research method used is qualitative and data is obtained from the Library Research method or literature research. The application of SERS, especially in humans, must involve various ethical perspectives such as patients, families, experimental animals and civil society. The context of SERS use is based on equal treatment of individuals, institutions and communities as well as the distribution of tools that are accessible to all groups and affordable and pay attention to the context of user welfare and autonomy. SERS regulations have been made by countries in Europe and the United States by creating very detailed standardization and procedures for using the tool so as not to cause dangerous side effects. In the view of Islamic law, SERS must pay attention to procedures that do not violate other Islamic principles, such as patient privacy and protection of sensitive body integrity.